x+2=4x(x-3)

Simple and best practice solution for x+2=4x(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2=4x(x-3) equation:


Simplifying
x + 2 = 4x(x + -3)

Reorder the terms:
2 + x = 4x(x + -3)

Reorder the terms:
2 + x = 4x(-3 + x)
2 + x = (-3 * 4x + x * 4x)
2 + x = (-12x + 4x2)

Solving
2 + x = -12x + 4x2

Solving for variable 'x'.

Combine like terms: x + 12x = 13x
2 + 13x + -4x2 = -12x + 4x2 + 12x + -4x2

Reorder the terms:
2 + 13x + -4x2 = -12x + 12x + 4x2 + -4x2

Combine like terms: -12x + 12x = 0
2 + 13x + -4x2 = 0 + 4x2 + -4x2
2 + 13x + -4x2 = 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
2 + 13x + -4x2 = 0

Begin completing the square.  Divide all terms by
-4 the coefficient of the squared term: 

Divide each side by '-4'.
-0.5 + -3.25x + x2 = 0

Move the constant term to the right:

Add '0.5' to each side of the equation.
-0.5 + -3.25x + 0.5 + x2 = 0 + 0.5

Reorder the terms:
-0.5 + 0.5 + -3.25x + x2 = 0 + 0.5

Combine like terms: -0.5 + 0.5 = 0.0
0.0 + -3.25x + x2 = 0 + 0.5
-3.25x + x2 = 0 + 0.5

Combine like terms: 0 + 0.5 = 0.5
-3.25x + x2 = 0.5

The x term is -3.25x.  Take half its coefficient (-1.625).
Square it (2.640625) and add it to both sides.

Add '2.640625' to each side of the equation.
-3.25x + 2.640625 + x2 = 0.5 + 2.640625

Reorder the terms:
2.640625 + -3.25x + x2 = 0.5 + 2.640625

Combine like terms: 0.5 + 2.640625 = 3.140625
2.640625 + -3.25x + x2 = 3.140625

Factor a perfect square on the left side:
(x + -1.625)(x + -1.625) = 3.140625

Calculate the square root of the right side: 1.77218086

Break this problem into two subproblems by setting 
(x + -1.625) equal to 1.77218086 and -1.77218086.

Subproblem 1

x + -1.625 = 1.77218086 Simplifying x + -1.625 = 1.77218086 Reorder the terms: -1.625 + x = 1.77218086 Solving -1.625 + x = 1.77218086 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.625' to each side of the equation. -1.625 + 1.625 + x = 1.77218086 + 1.625 Combine like terms: -1.625 + 1.625 = 0.000 0.000 + x = 1.77218086 + 1.625 x = 1.77218086 + 1.625 Combine like terms: 1.77218086 + 1.625 = 3.39718086 x = 3.39718086 Simplifying x = 3.39718086

Subproblem 2

x + -1.625 = -1.77218086 Simplifying x + -1.625 = -1.77218086 Reorder the terms: -1.625 + x = -1.77218086 Solving -1.625 + x = -1.77218086 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.625' to each side of the equation. -1.625 + 1.625 + x = -1.77218086 + 1.625 Combine like terms: -1.625 + 1.625 = 0.000 0.000 + x = -1.77218086 + 1.625 x = -1.77218086 + 1.625 Combine like terms: -1.77218086 + 1.625 = -0.14718086 x = -0.14718086 Simplifying x = -0.14718086

Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.39718086, -0.14718086}

See similar equations:

| 90+2x=180 | | 2m-(4m+12)=6 | | 5-5y+y-1=-23 | | 3.8=m+1.7 | | 2(x-1)+6=-3(x+8) | | -.4n=3.2 | | -49+-r=-76 | | p-6=-14 | | -10=-12+.57n | | x^2+23+10x-6=136 | | 75+35h=180 | | (6y+5)-5(3y+2)=2(2y-9) | | -7x-11y=48 | | 3(t+2)=4t | | 2h^2+4h+4=576 | | 8s+-13=-77 | | x+2=2x^2-4 | | 6n-36=n+9 | | 3(y+3)-2(y-1)=0 | | x+9=-3*2 | | 23=16+7q | | 23=16+7a | | 2.2x-7-1.6x=0.6x-7 | | 2(x+4)=3x-1*5 | | 7g-1=13-5g | | n-6=2-3n | | -4y+8(7y-2)=5-4(-4-y) | | Y-44=-27 | | x+4=20x | | x+4=10x | | 2a(a-5)+4(a-5)=a | | 101(3a-1)=149 |

Equations solver categories